Congress of the Polish Chamber of Tourism - Egypt 2017 - Marek Napierała; Jerzy Matuszak; Walery Zukow (Kazimierz Wielki University, 2017)
The aim of the article is to assess the effectiveness of the Congress of the Polish Chamber of Tourism 2017 in the elaboration of joint applications regarding the provision of substantive and logistical support to entrepreneurs as well as the pursuit of comprehensive regulation of tourism law; adaptation of Polish law to European standards. Research problems: What is the legal status in the field of tourism law regarding outgoing tourism, incoming tourism and MICE, children and youth tourism, domestic tourism and accommodation facilities, travel agents and air transport? What are the main problems of the industries and what are their solutions proposed? What is the position and conclusions of the Congress? Research methods: study of documents, source materials, study of Congress materials, interviews with participants of the Congress, personal participation in the Congress. The PIT Congress took place on 25.11. - 2.12.2017 in Egypt (Marsa Alam): "Groundbreaking changes in tourism law: challenges and problems". The aim of the Congress was to develop a common position in the field of tourism law on outgoing tourism, incoming tourism and MICE, children and youth tourism, domestic tourism and accommodation facilities, travel agents and air transport. PIT is the largest nationwide organization of the economic self-government of the tourism industry. Polish Chamber of Tourism, which is a full member of the European Union of Travel Agencies of the European Union (ECTAA). From the beginning of its existence (25 years of activity), it has been successfully applying for a new shape of tourist business in Poland. Conclusions: - trainings should be carried out using the latest laws, - substantive and logistical support should be provided to entrepreneurs, - strive for comprehensive regulation of tourism law, - tourism needs a host so that it can be prioritized as an important branch of the economy.